2009
DOI: 10.1177/103841620901800206
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gender on Career Readiness among Malaysian Undergraduates

Abstract: This study aimed to investigate the influence of gender on career readiness among Malaysian undergraduate students at Malaysian universities. Data were collected via a self-administered questionnaire of 1229 Malaysian undergraduate students from four public universities. Respondents were identified through the multistage stratified sampling method. Findings of the study indicate that a majority of the respondents reported low level of career readiness. When compared to male undergraduates, female undergraduate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…This was not the case with our data. However, previous literature measuring career readiness in other contexts found mixed results, with some reporting limited or no relationship (Hirschi & Läge, 2007) and other studies finding gender differences in career readiness (Mansor & Tan, 2009). Analyses of gender on individual items in the SCRI revealed no significant differences other than on the item, "I will continue to work on my studies even when I get frustrated."…”
Section: Demographic Variablesmentioning
confidence: 78%
“…This was not the case with our data. However, previous literature measuring career readiness in other contexts found mixed results, with some reporting limited or no relationship (Hirschi & Läge, 2007) and other studies finding gender differences in career readiness (Mansor & Tan, 2009). Analyses of gender on individual items in the SCRI revealed no significant differences other than on the item, "I will continue to work on my studies even when I get frustrated."…”
Section: Demographic Variablesmentioning
confidence: 78%
“…Significant differences were found between male and female under-graduate students for career readiness. 37 Another study also identified differences in interpersonal skills, team work skills, communication skills, and organizational skills on the basis of gender. 38 The pragmatics of career choice differs with the lower and higher socio-economic status of high school students.…”
Section: Association Of Student’s Readiness and Orientation (Underratmentioning
confidence: 99%
“…It highlights the concern of the rising trend of Malaysia's unemployment rate, considering the pandemic situation as well. These statistics of the unemployment rate among graduates remains a serious concern and it is deemed to be attributable by students' lack of career readiness and maturity, putting aside the changing economic landscape and labour market impacted by the COVID-19 (Mansor & Tan, 2009). With limited knowledge and awareness of the professional world, students are pushed and pressured to figure out what career they should pursue even though they may be clueless about what they may want to do in the future.…”
Section: Introductionmentioning
confidence: 99%
“…With limited knowledge and awareness of the professional world, students are pushed and pressured to figure out what career they should pursue even though they may be clueless about what they may want to do in the future. Moreover, from a theoretical standpoint, final year university students aged between 21 to 23 years old should have been able to crystallise and specify their career options according to career developmental tasks (Mansor & Tan, 2009). The ability to make a right career decision is of utmost importance as it has a lifelong impact on one's life, and it can be taxing and stressful on students as well knowing the consequences of making a wrong career decision.…”
Section: Introductionmentioning
confidence: 99%